2010
DOI: 10.1371/journal.pone.0009433
|View full text |Cite
|
Sign up to set email alerts
|

A Demonstration of the Transition from Ready-to-Hand to Unready-to-Hand

Abstract: The ideas of continental philosopher Martin Heidegger have been influential in cognitive science and artificial intelligence, despite the fact that there has been no effort to analyze these ideas empirically. The experiments reported here are designed to lend empirical support to Heidegger's phenomenology and more specifically his description of the transition between ready-to-hand and unready-to-hand modes in interactions with tools. In experiment 1, we found that a smoothly coping cognitive system exhibits … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
110
0
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
4
3
3

Relationship

0
10

Authors

Journals

citations
Cited by 108 publications
(117 citation statements)
references
References 27 publications
5
110
0
2
Order By: Relevance
“…Other studies have identified Heidegger's readiness-to-hand phenomenon using a mouse [5], in which the mouse controls a pointer on Number of Rotations the screen, but failed to link the tool directly to the person interacting with it. Our results show a direct link between tool use and being ready-to-hand, where attentional shift was observed in both physical and virtual tools.…”
Section: Discussionmentioning
confidence: 99%
“…Other studies have identified Heidegger's readiness-to-hand phenomenon using a mouse [5], in which the mouse controls a pointer on Number of Rotations the screen, but failed to link the tool directly to the person interacting with it. Our results show a direct link between tool use and being ready-to-hand, where attentional shift was observed in both physical and virtual tools.…”
Section: Discussionmentioning
confidence: 99%
“…In part, this reflects the motor component of the activity being studied and the ability of people to adapt to situational demands as embodied systems. For example, Dotov et al (2010) demonstrate that hand-mouse coordination in a simple video game exhibits 1/f scaling during normal operation but not when the task is disrupted. This indicates that, during normal operation, hand-mouse control can be described as an interaction-dominant system.…”
Section: Dexterity Dynamics and Tool Usementioning
confidence: 99%
“…Por ejemplo, estudios sobre tareas de lectura en personas con dislexia ha evidenciado que el funcionamiento lector normal sigue dinámicas dominadas por la interacción de procesos de tipo ruido rosa, mientras que las disfuncionalidades de los disléxicos están provocadas por funcionamientos en los que la dinámica está dominada por los componentes del sistema, acercándose a procesos de ruido blanco, evidenciando una falta de coordinación entre los diferentes módulos neuronales que participan en la tarea (Wijnants et al, 2012). Similarmente, la soltura en el manejo de una herramienta está indicada por la presencia de ruido rosa, mientras que cuando el sistema es perturbado provocando que la interacción sea problemática el valor de β se reduce (Dotov et al, 2010). Estos estudios sugieren que mientras que las medidas de ruido blanco representan procesos en los que la dinámica global consisten en la suma de dinámicas individuales de los componentes del sistema, en los procesos de ruido rosa se consigue alcanzar un equilibrio entre las dinámicas individuales de los componentes del sistema y la dinámica global del sistema, mostrando un tipo de dinámica especial dominada por la interacción continua entre los diferentes componentes de un sistema (Van Orden et al, 2003).…”
Section: Miguel Aguilera Encuentro Transdisciplinarunclassified